2020
DOI: 10.1016/j.psj.2020.06.062
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of commercial polyvalent avian infectious bronchitis vaccines against Chinese QX-like and TW-like strain via different vaccination strategies

Abstract: The infectious bronchitis virus ( IBV ) is an acute and highly contagious disease, which affects chickens of all ages. Vaccination is the most important way to control this disease. Nevertheless, novel variant strains are constantly reported because of the lack of proofreading capabilities of RNA polymerase and high frequency of homologous RNA recombination. Cross-protection studies has demonstrated that the vaccines could provide great protective effects against viruses of same serotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The current approach to commercial vaccination typically takes the form of immunization with two antigenically diverse IBV variants selectively complemented with an inactivated vaccine for layers [138]. Commercial IBV vaccines are generally administered early in life starting with day-old chicks [136].…”
Section: Infectious Bronchitis Virus (Ibv) and Vaccination Strategymentioning
confidence: 99%
“…The current approach to commercial vaccination typically takes the form of immunization with two antigenically diverse IBV variants selectively complemented with an inactivated vaccine for layers [138]. Commercial IBV vaccines are generally administered early in life starting with day-old chicks [136].…”
Section: Infectious Bronchitis Virus (Ibv) and Vaccination Strategymentioning
confidence: 99%
“…Several alternative options have been applied to provide broad protection against variant IBV strains, including recombinant vaccine ( Li et al, 2016 ), nanoparticle-based vaccine ( Li et al, 2018 ), epitope-based vaccines ( Qin et al, 2021 ), etc., but they have yet to be administrated with mass hatchery application. In addition, considering multi-monovalent live attenuated vaccines, though several research showed efficacy in control different IBV strains in a laboratory scale ( Shao et al, 2020 ; Abdel-Sabour et al, 2021 ), it still raises many issues including the frequency of combination among field and vaccine strains ( Bali et al, 2021 ). Therefore, proper selection of the vaccine and vaccination strategy is highly important to control the disease in the field.…”
Section: Discussionmentioning
confidence: 99%
“…In IBV, suboptimal vaccination alters the evolutionary dynamics of the viruses and can contribute to the production of escape mutants [122][123][124]. Finding broadly neutralizing IBV vaccines remains a significant challenge for the poultry industry [125][126][127][128][129].…”
Section: Harms Of Coronavirus Vaccinationmentioning
confidence: 99%